Light-enabled alkenylation of iodocarboranes with unactivated alkenes. Issue 1 (6th December 2021) - Ni, Hangcheng; Lu, Zhenpin; Xie, Zuowei
Abstract : Transition metal-free photoalkenylation of iodocarboranes with unactivated alkenes has been achieved for the facile synthesis of alkenylated- o -carboranes with broad substrate scope and good functional group tolerance under mild reaction conditions. Abstract : The synthesis of alkenylated- o -carboranes via photoalkenylation of iodocarboranes with unactivated alkenes has been achieved. This strategy features a transition metal-free protocol, a light-promoted reaction under mild reaction conditions, broad substrate scope and good functional group tolerance. Control experiments suggest that the reaction may involve the cage C-centered radical species.